Tetracyclines are Associated with a Reduced Risk of Clostridium difficile Infection: A Systematic Review and Meta-analysis. (4th October 2017) - Tariq, Raseen; Cho, Janice; Kapoor, Saloni; Orenstein, Robert; Singh, Siddharth; Pardi, Darrell; Khanna, Sahil
Abstract: Background: Efforts towards antibiotic stewardship help reduce risk of Clostridium difficile infection (CDI) but there is a need to delineate antibiotic choices to reduce CDI risk. Tetracyclines may be associated with a low risk for CDI but the evidence is conflicting. We conducted a systematic review and meta-analysis to determine the relationship between tetracyclines use and CDI. Methods: A systematic search of Medline, Embase, and Web of Science was performed from January 1978 up to December 2016 including studies assessing the association between tetracyclines and CDI; compared with other antibiotics; to assess the risk of CDI after exposure to tetracyclines vs. other antibiotics. Study quality was assessed using the Newcastle-Ottawa scale. Weighted summary estimates were calculated using generalized inverse variance with random-effects model using Review Manager version 5.3 (Cochran Inc). Results: Six studies; 4 case control and 2 cohort studies reported the association of CDI with tetracyclines or other antibiotics prior to CDI including patients from 1993 to 2012. Meta-analysis of all studies using the random-effects model demonstrated that tetracyclines were associated with decreased risk of CDI compared with other antibiotics (OR, 0.62; 95% CI, 0.47–0.81; P = .0005). There was significant heterogeneity among the studies, with an I 2 of 53% (Figure 1). No publication bias was seen. Subgroup analysis of studies evaluating the risk of CDI with doxycycline only also demonstrated a decreased risk of CDI with doxycycline compared with other antibiotics (OR, 0.55; 95% CI, 0.40–0.75; P = 0.0002). A subgroup analysis based on CDI diagnosis definitions revealed a decreased risk of CDI with tetracyclines (OR, 0.59; 95% CI, 0.44–0.80; P = 0. 0006) in studies that used clinical definitions (presence of diarrhea with a positive stool test), but not among the studies that used ICD-9 codes for CDI diagnosis (OR, 0.95; 95% CI, 0.45–2.01; P =  0.90). Conclusion: Tetracyclines are associated with a lower risk of developing CDI compared with other antibiotics. It is reasonable to use these over other antibiotics when appropriate (community acquired pneumonia, bronchitis, chlamydia, rickettsial or spirochetal infections) to reduce the risk of CDI. Forest plot demonstrating decreased odds of CDI with tetracyclines use by a random-effects model Disclosures: All authors: No reported disclosures.